EFFECT OF LEARNING MODEL MAKE A MATCH THE RESULTS STUDENT LEARNING MATERIALS IN DRAWING TECHNIQUES IN MOTORCYCLE TECHNIQUE CLASS X SMK NEGERI 1 PALANGKA RAYA 2015/2016 ACADEMIC YEAR - Aditama; Sanggam R.I. Manalu (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2017)
In the learning process, the teachers still rely on conventional learning model without making the variation which is more interesting, conducive and pleasant in classroom atmosphere. Teachers stated that students understand the material that has been taught without trying to confirm the students' understanding of the material. This causing the active role of students in learning does not be achieved, and students tend to be passive in the learning process at school. With these activities, the value of students during the learning to use the lecture method is very low in which at below average value 65. The minimum completeness standard is at 70 that there should be an improvement in the learning activities to increase students' grade. It would be achieve Namely by using model The Make A Match students. This can be active and focus on learning also noticed that students can exchange ideas and information inter classmates. The purpose of this study to determine whether there is influence between the learning outcomes of students taught by conventional methods on the material in class X Drafting TSM SMK 1 Palangka Raya. The sampling was conducted using random sampling techniques. Samples were first involved 30 students in class TSM as class experiments using model-type Make A Match and the second sample envolved 33 students in class as a class TKR control using conventional learning models based on the teaching and researching as the kind of experiment. In the present study, the instrument is in the form of multiple-choice tests to collect data of student learning outcomes. Data was analyzed with normality test, homogeneity, and the t-test, the normality test for the Post Test Experiment class is x²counting <x²tablel, namely 8.61 <11.070. Post Test and Normality test grade control x²hitung <x²tablel, namely 8.21 <11.070, to obtain homogeneity test of F = (0,42) <F table (2.37), and other homogeneous. Finally we can conclude that t-test obtained t = 3.7> TTable = 2.000 then H_o H_1 can be accepted. H_1 is influenc of student learning outcomes significantly between using model Make A Match, with the use of conventional learning models in class X SMK Negeri 1 Palangkaraya at academic year 2015/2016.